Occurrence of ACE-inhibitory di- and tripeptides in oat storage proteins - Loponen, Jussi; Laine, Pia (MTT, 2004)
Angiotensin I-converting enzyme (ACE) regulates blood pressure by its hydrolytic actions. Certain food-derived peptides with appropriate structures inhibit the activity of ACE. This study aimed to show the occurrences and locations of known ACE-inhibitory peptides in the structures of oat storage proteins, globulins and avenins. Liberation of the target peptides is also discussed. The primary structures of oat globulins and avenins were explored in a protein structure database environment (iProClass) for the known ACEinhibitory di- and tripeptides (IC50-value 10µM or less). In order to hypothesize, which enzymes could release the target peptides, the structural properties and locations of the found peptide sequences were analysed. Of the searched ACE-inhibitory peptides, ten occurred in oat storage proteins. Oat 11S globulins contained four dipeptides and three tripeptides, whereas three dipeptides and two tripeptides occurred in avenin structures. Some of the dipeptides had multiple occurrences in avenins and globulins, which make them an interesting target peptide group. Structural analysis revealed that nine of the peptides found in oat storage proteins had an aliphatic amino acid in N-terminus, whereas four of the five tripeptides had proline in their C-terminus. Thus in theory, to liberate these kind of peptides from the structures of oat storage proteins a selective protease that cleaves peptide bonds before aliphatic amino acids could be used together with a proline specific enzyme that cleaves peptide bonds after proline. The storage proteins of oats thus appeared to be potential sources of ACEinhibitory peptides. The liberation of these peptides during food processing, however, requires safe and selective enzymes, and suitable hydrolysis conditions for both the enzymes and the substrate proteins.
Keywords: Ka; ACE; peptides; oat; globulin; avenin; protease